Efeitos do tratamento da curcumina (Curcuma longa) associada à prednisona em ratas Wistar em processo de envelhecimento com artrite reumatoide - Retameiro, Ana Caroline Barbosa (2024)
Rheumatoid arthritis (RA) is an inflammatory, autoimmune and systemic disease that is more prevalent in women aged between 40 and 50 years old, and mainly affects synovial joints and periarticular structures. Standard treatment includes the use of glucocorticoids, including prednisone (PD), which has numerous associated side effects such as: gastrointestinal, cardiovascular, endocrine, neuropsychiatric, dermatological, ocular and immunological disorders. Therefore, alternative therapies, including the use of supplementation with herbal medicines, such as curcumin (CM), have been tested, due to its anti-inflammatory, antioxidant and antiarthritic properties. In the present work, we analyzed the effect of CM supplementation in PD treatment on the functionality of the hind paw, morphological, inflammatory and immunological aspects of the tibiofemoral joint and its periarticular structures and on the histomorphometric and immunohistochemical aspects of the rectus femoris muscle. For this, thirty 18-month-old female Wistar rats were distributed into six (APLD), arthritis PD high-dose (APHD) and arthritis PD low-dose and CM (APLDC). The experimental RA was induced by a complete Freund’s adjuvant injection (CFA) into the right tibiofemoral joint cavity. The treatment with PD (2mg/kg/day and 10mg/kg/day) and CM (100mg/kg/day), using gavage method, was performed for 14 consecutive days. The functional aspects of grip strength, nociceptive threshold, proprioception and joint capacity, were evaluated in the pelvic limb; immunological, immunohistochemical and histomorphometric evaluations were performed in blood plasma, popliteal lymph node, rectus femoris muscle and tibio femoral joint, respectively. For statistical analysis, the generalized linear model test was used in the Statistical Package for the Social Sciences (SPSS) program. The significance level was set as p=0.05. The groups AC and APLD had improvements in grip strength and motor function. When compared to GC, AC and APLDC had positive effects on the concentrations of lipoperoxidation (p=0.2; p=0.69), tumor necrosis factor α (p=0.080; p=0.346) and leukocyte migration (p=0.013). In the morphological 11 and semiquantitative aspects of the tibiofemoral joint, inflammatory aspects of the periarticular structures and muscles, AC and APLDC had the most promising results. Regarding histomorphometric and immunohistochemical analysis of the rectus femoris muscle, APDBC showed the best morphological aspects (p<0.0001). Therefore, it was possible to conclude that supplementation with 100 mg/kg/day of CM, in treatment with low dose of 2mg/kg/day of PD restored functional capacity, inflammatory, immunological and histomorphometric aspects in old female rats with experimental RA, resembling the standard dose of the medication used to treat the disease.